THE IMPORTANCE, TASKS AND SOURCES OF INFORMATION OF THE ANALYSIS OF PRODUCTION AND SALES PROCESSES OF ENTERPRISES - A.X.Choriyev; I.B.Sapayev; H.S.Saydazimov; G.S.Xaydarova; J.G’.Tursunov; M.M.Yarbekova; M.T.Bazarbayeva; T.J.Berdiyev; E.Q.Djurayeva; M.S.Buranov; S.R.Abdullayev; M.O.Erkinova; et al. (INTERNATIONAL JOURNAL OF RESEARCH IN COMMERCE, IT, ENGINEERING AND SOCIAL SCIENCES ISSN: 2349-7793 Impact Factor: 6.876, 2023)
In the leading industries operating in the Republic of Uzbekistan, programs for various periods of modernization of production, technical and technological re-equipment and transition to international quality standards have been developed and are being consistently implemented. In a context of declining demand in the world market, supporting domestic producers by stimulating demand in the domestic market is critical to maintaining high rates of economic growth.